Comparative genomics and synteny analysis of PP2C phosphatases in modern and wild sugarcane cultivars for insights into abiotic stress response - Shweta Kumari; R. K. Harshavardhini; Nandhini Murugan; S. Keerthana; Aispriya; Vinayaka; Anitha Ramaswamy; Jeyakumar Prabhakaran; Manimekalai Ramaswamy (Frontiers in Plant Science)
PP2C phosphatases regulate key physiological processes in plants, essential for growth, development, and stress responses. Sugarcane, a vital crop for many economies, faces severe abiotic stress, which negatively impacts production. Given the role of the PP2C gene family in stress tolerance and the recent publication of the genome sequence of the modern polyploid sugarcane cultivar R570, this study conducted genome-wide identification and characterization of the PP2C gene family in sugarcane. The analysis includes genome-wide identification, phylogenetic analysis, gene structure, conserved motif and domain analysis, synteny analysis, evolutionary selection pressure (Ka/Ks) estimation, gene ontology annotation, and RT-qPCR based expression profiling of selected PP2C genes. A total of 500 PP2C genes were identified, distributed across all 10 chromosomes and their subgenomes. Phylogenetic analysis, using Arabidopsis, S. spontaneum, maize, and wheat as references, classified these genes into 13 subfamilies. The results showed that, similar to S. spontaneum, where the largest subfamily is F with 37 members, the largest subfamily in the sugarcane hybrid cultivar was also F, with 74 members, followed by subfamily A with 69 members. The exon and motif distribution were found to be highly conserved within the same subfamily. Tandem duplication was prominent, with 107 genes identified as paralogs, indicating their role in gene expansion. The chromosomal distribution of SoffiXPP2C genes was partially biased, as approximately 50% of the genes were located on chromosomes 1, 2, and 3, along with their respective subgenomes. Synteny analysis revealed a strong conservation of the protein phosphatase domain between modern hybrid and wild sugarcane (S. spontaneum). Additionally, the synteny association of SoffiXPP2C genes with two potential cold stress-responsive genes, SsPP2C27 and SsPP2C64, suggests a possible role of SoffiXPP2C genes in abiotic stress regulation. The observed downregulation of certain SoffiXPP2C genes in waterlogging-tolerant genotypes further supports their potential function as negative regulators, particularly under waterlogging stress conditions. The domain architecture analysis further emphasizes the multifaceted roles of sugarcane PP2Cs, particularly in stress signaling, protein phosphorylation regulation, and membrane-associated functions. Furthermore, the strong alignment of 34 SoffiXPP2C genes with differentially expressed contigs of sugarcane under oxidative stress conditions reinforces insights into the potential role of SoffiXPP2Cs in stress response. These findings provide valuable insights into the evolutionary conservation of PP2C genes in sugarcane hybrid cultivar and their critical role in abiotic stress responses.